2009
DOI: 10.1093/ndt/gfp435
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3-enriched infiltrates associated with better outcome in renal allografts with inflamed fibrosis

Abstract: Our results suggest that Tregs may dampen the graft injury in chronic (versus acute) inflammation and stress the importance of devising strategies to enhance Tregs efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
3
24
1
3
Order By: Relevance
“…Indeed, IL-10-producing Tregs were detected in the interstitium of rejected grafts and enrichment in IL-10 was observed in the cytokinic microenvironments of the slow progressor grafts. These data suggest that Tregs play an important role in slowing down the chronic rejection process, as previously proposed (9)(10)(11). On the other hand, it is important to note that renal grafts from the two groups displayed similar levels of infiltration by immune effectors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, IL-10-producing Tregs were detected in the interstitium of rejected grafts and enrichment in IL-10 was observed in the cytokinic microenvironments of the slow progressor grafts. These data suggest that Tregs play an important role in slowing down the chronic rejection process, as previously proposed (9)(10)(11). On the other hand, it is important to note that renal grafts from the two groups displayed similar levels of infiltration by immune effectors.…”
Section: Discussionsupporting
confidence: 82%
“…These works have led to the conclusion that the grafts may be destroyed indifferently by Th1, Th2 (5, 6), or Th17 (7,8) cells, although with variable kinetics and through different pathogenic mechanisms. In contrast, Tregs appeared to exert a protective effect against rejection (9)(10)(11). However, because most of these studies have been conducted in transgenic murine experimental models, the validity of the findings in a clinical chronic rejection setting remains largely elusive.…”
mentioning
confidence: 99%
“…6,7,35 In accordance with these findings, lower frequencies of Tregs have been correlated with poor graft outcomes. 4,11,34,36 Despite accumulating data from various experimental models, the present clinical results are insufficient to prove that Tregs play a role in the maintenance of tolerance in operationally tolerant recipients. In this article, we report on increased Foxp3 demethylation and a higher frequency of circulating mTregs in the blood of tolerant recipients compared with nontolerant equivalents and healthy controls.…”
Section: Discussionmentioning
confidence: 79%
“…32 Alternatively, this phenomenon could not indicate alloimmunity, but simply reflect the process of natural stabilization of inflamed sites operated by T regulatory cells, not associated with better graft survival, as suggested by Bunnag et al 12 These authors reported increased FOXP3 expression in late kidney allograft biopsies as compared to early biopsies, which was correlated with inflammation, injury, and repair assessed by pathogenesis-based transcript microarrays.…”
Section: Discussionmentioning
confidence: 96%